2022
DOI: 10.2306/scienceasia1513-1874.2022.092
|View full text |Cite
|
Sign up to set email alerts
|

KLF7 promotes LPS induced apoptosis, inflammation, and oxidative stress in H9c2 cells by activating NF-κB pathway

Abstract: This study aimed to investigate and explore the molecular mechanisms of Krüppel-like factor 7 (KLF7) on apoptosis, inflammation, and oxidative stress in H9c2 cells. In the study, the protein expression of KLF7 in H9c2 cells were ascertained by western blot after lipopolysaccharide (LPS) treatment and small interfering RNA (siRNA) transfection. The results confirmed that the expression levels of the protein KLF7 were dramatically increased after LPS treatment and decreased after siRNA transfection. Then, the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For instance, the latest research found that KLF7 can promote LPS induced apoptosis, inflammation, and oxidative stress in H9c2 cells by activating NF-κB pathway. Knocking down KLF7 could be a therapeutic method to treat sepsis (diseases related to abnormal cell inflammation) [39]. KLF7 could become a potential drug target for the treatment of sepsis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the latest research found that KLF7 can promote LPS induced apoptosis, inflammation, and oxidative stress in H9c2 cells by activating NF-κB pathway. Knocking down KLF7 could be a therapeutic method to treat sepsis (diseases related to abnormal cell inflammation) [39]. KLF7 could become a potential drug target for the treatment of sepsis in the future.…”
Section: Discussionmentioning
confidence: 99%